Type Collections of Drosophilidae (Diptera). I. The Strobl Collection. - Basden, Eric Bernard (Contributions to Entomology = Beiträge zur Entomologie, 1961)
1. A critical review is presented of the 308 specimens of Drosophilidae (s. str.) in Strobl’s collection at Graz, Austria. A total of 68 species or their synonyms is discussed. Some new synonymy is proposed. A few MS names and nomina nuda are exposed. - 2. Lordiphosa n. subgen. is proposed for the fenestrarum group of Drosophila. - 3. Types of the following species are here selected (original genus given): Stegana nigrithorax Str., St. stroblii Mik, Phortica obscuripes Str., Drosophila nigrosparsa Str., D. tinctipennis Str., D. andalusiaca Str., D. nigricolor Str., D. unimaculata Str., and D. unistriata Str.; and the type association of D. nigrithorax Str. is determined. Nomenclatural Acts atrimana Strobl, 1910 (Camilla), Lectotype described as Camilla glabra var. atrimana rufipes (Strobl, 1893) (Camilla), Lectotype described as Noterophila rufipes andalusiaca Strobl, 1906 (Drosophila), Lectotype Loridophosa Basden, 1961 (Drosophila), sgen. n. nigricolor Strobl, 1898 (Drosophila), Lectotype tinctipennis Strobl, 1901 (Drosophila), Lectotype described as Drosophila obscura var. tinctipennis unimaculata Strobl, 1893 (Drosophila), Lectotype unistriata Strobl, 1898 (Drosophila), Lectotype; syn. n. of Drosophila cameraria Haliday, 1856 nigrosparsa Strobl, 1898 (Drosophila (Spinodrosophila)), Lectotype described as Drosophila nigrosparsa nigripes Strobl, 1898 (Noterophila), Lectotype described as Noterophila acutipennis var. nigripes obscuripes (Strobl, 1910) (Phortica), Lectotype described as Amiota albilabris obscuripes stroblii Mik, 1898 (Stegana), Lectotype